2022
DOI: 10.1007/s11250-022-03106-w
|View full text |Cite
|
Sign up to set email alerts
|

Performance and feeding behavior of Holstein and Holstein × Gyr crossbred heifers grazing temperate forages

Abstract: This study aimed to investigate the difference between Holstein and Holstein x Gyr breeds on feeding behavior and performance of heifers grazing temperate pasture. The experiment was carried out in 89 days, split into 14 days of adaptation and 3 periods of 25 days. Two treatments were used: Holstein (HOL; n = 7) and Holstein × Gyr (HG; n = 7). Heifers grazed a consortium of ryegrass and Bristle Oats and were supplemented individually daily with corn meal at 0.33% of body weight plus 5 kg/d of corn silage. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, Holstein and crossbred genetics have been modified over the years ( Washburn and Mullen, 2014 ), and the mechanisms behind different performance responses of purebred or crossbred young animals in tropical pasture-based systems are not fully understood. Abreu et al (2022) suggested that Holstein heifers have less heat tolerance, demonstrated by the greater bite rate (20 vs. 17.3), and shorter grazing time spent in each meal compared to crossbred heifers. Therefore, the variation in performance of Holstein × Gyr and Holstein heifers might be explained by the ability to graze in high temperatures, which consequently impacts time spent in grazing and resting ( Quirino et al, 2022 ), resistance to ectoparasites, and susceptibility to infectious diseases ( Otto et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Holstein and crossbred genetics have been modified over the years ( Washburn and Mullen, 2014 ), and the mechanisms behind different performance responses of purebred or crossbred young animals in tropical pasture-based systems are not fully understood. Abreu et al (2022) suggested that Holstein heifers have less heat tolerance, demonstrated by the greater bite rate (20 vs. 17.3), and shorter grazing time spent in each meal compared to crossbred heifers. Therefore, the variation in performance of Holstein × Gyr and Holstein heifers might be explained by the ability to graze in high temperatures, which consequently impacts time spent in grazing and resting ( Quirino et al, 2022 ), resistance to ectoparasites, and susceptibility to infectious diseases ( Otto et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cactus forage has been intensively studied since 1972 by research institutes in Brazil and countries such as South Africa, Mexico, Morocco, and Tunisia [ 5 , 6 , 7 ], and today it is recognized as an energy (metabolizable energy = 2.38 Mcal/kg DM) [ 8 ] and water source for livestock in semiarid regions. Among several species studied, the most used and resistant to eventual pests in Brazilian semiarid areas are the forage cactus Miúda (NUB) ( Nopalea cochenillifera Salm–Dyck) and Mexican Elephant Ear (OUB) ( Opuntia stricta [ Haw ] Haw).…”
Section: Introductionmentioning
confidence: 99%